2017
DOI: 10.3390/w9080584
|View full text |Cite
|
Sign up to set email alerts
|

Multi–Model Ensemble Approaches to Assessment of Effects of Local Climate Change on Water Resources of the Hotan River Basin in Xinjiang, China

Abstract: Abstract:The effects of global climate change threaten the availability of water resources worldwide and modify their tempo-spatial pattern. Properly quantifying the possible effects of climate change on water resources under different hydrological models is a great challenge in ungauged alpine regions. By using remote sensing data to support established models, this study aimed to reveal the effects of climate change using two models of hydrological processes including total water resources, peak flows, evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…The SWAT model is a semi-distributed, physically-based, and time-continuous hydrological model that was developed by the United States Department of Agriculture's Agricultural Research Service (USDA-ARS) [37]. This model requires spatial information related to land use information, meteorological variables, soil textural and physicochemical properties, and topography [38]. It divides a basin into sub-basins that include topographic information and the sub-basins are further divided into minimum hydrologic response units (HRUs) that uniquely combine land use, slope, and soil type [39].…”
Section: Hydrological Modellingmentioning
confidence: 99%
“…The SWAT model is a semi-distributed, physically-based, and time-continuous hydrological model that was developed by the United States Department of Agriculture's Agricultural Research Service (USDA-ARS) [37]. This model requires spatial information related to land use information, meteorological variables, soil textural and physicochemical properties, and topography [38]. It divides a basin into sub-basins that include topographic information and the sub-basins are further divided into minimum hydrologic response units (HRUs) that uniquely combine land use, slope, and soil type [39].…”
Section: Hydrological Modellingmentioning
confidence: 99%
“…In recent years, the Earth's water cycle has changed due to the impact of global changes and human activities [1], and many countries or regions worldwide are facing serious water problems and crises [2,3]. Water problems have become a key factor restricting national and regional sustainable development [4]. Current water problems are mostly related to irrational human development activities, and various studies have shown that these impacts may outweigh the effects of other global changes [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Five other studies [10,14,[16][17][18] belong more properly to the category "Climate change impact studies". The last three studies [24][25][26] analyze changes that have occurred in the climate and with water resources in the recent past decades, without developing any future scenarios. However, in all these last eight studies, the component related to the "adaptation to climate change" is present, but not fully developed, i.e, they are unbalanced in favor of the assessment of future impacts and less towards the adaptation.…”
Section: Studies For the Development Of Adaptation Scenariosmentioning
confidence: 99%